PENGARUH KERJASAMA, KOMUNIKASI DAN DISIPLIN KERJA TERHADAP KINERJA KARYAWAN PADA PARAMA SU HOTEL PALU - Arafah, Moh. Arafah; Petingko, Frengki (Jurnal Metaverse ADPERTISI, 2023)
The purpose of this research is to analyze the influence of cooperation, communication and work discipline variables on employee performance either simultaneously or partially. Data analysis using multiple linear regression analysis. The results of the analysis show that cooperation, communication and work discipline can improve employee performance well. If cooperation increases 100% then satisfaction is 33.7%. If communication increases 100% then satisfaction is 52.2%. Whereas. Meanwhile, if work discipline increases 100% then satisfaction increases 43.8%. The simultaneous correlation coefficient (Multiple R) = 0.595 means that cooperation, communication and work discipline have a moderate positive relationship with performance. Furthermore, the coefficient of determination Adjusted R Square 0.305 means that cooperation, communication and work discipline have an effect of 30% while the rest is in the variables not studied. The F test yields Fhiung (7.299) > Ftable (2.83) meaning that cooperation, communication and work discipline simultaneously have a significant effect on performance.